Mindfulness-Based Interventions for Young People With Cancer: An Integrative Literature Review. Issue 5 (September 2021) - Pathrose, Sheeja Perumbil; Everett, Bronwyn; Patterson, Pandora; Ussher, Jane; Salamonson, Yenna; McDonald, Fiona; Biegel, Gina; Ramjan, Lucie
Abstract : Background: Mindfulness-based interventions (MBIs) have demonstrated benefits for adults with chronic illness and are becoming increasingly popular among children and young people. Mindfulness-based interventions could have benefits for young people with cancer throughout the treatment journey, through to survivorship. Objective: The aim was to review intervention studies about MBI used with young people with cancer between the ages of 10 and 29 years. Methods: Six electronic databases were searched. The methodological quality of the included studies was assessed using the Joanna Briggs Institute critical appraisal tools. Results: Six contemporary studies met the inclusion criteria. Three studies adapted MBI to be age appropriate and some studies modified the intervention based on cancer-specific needs of young people. Formal and informal MBI activities were found to be acceptable by young people; however, recruitment of the participants was identified as a barrier. Variability in psychosocial outcomes was noted in the review by some demonstrating improvement in areas such as mindfulness, anxiety, and social isolation and others not eliciting significant benefits. Conclusions: Mindfulness-based intervention shows promise as an acceptable intervention that may improve psychosocial well-being for young people with cancer. Future research studies with adequate sample sizes are warranted to determine the effectiveness of MBI among young people with cancer. Implications for Practice: Mindfulness-based intervention seems to be a promising approach to promote psychosocial well-being and reduce disease burden in young people with cancer. As validated MBI may be implemented without expert training, this could be promoted by healthcare providers, including nurses who care for young people with cancer.